2013
DOI: 10.1111/j.1365-2125.2012.04364.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a herbal extract containing curcumin and piperine on midazolam, flurbiprofen and paracetamol (acetaminophen) pharmacokinetics in healthy volunteers

Abstract: AIMSTurmeric extract derived curcuminoids (curcumin, demethoxycurcumin and bisdemethoxycurcumin) are currently being evaluated for the treatment of cancer and Alzheimer's dementia. Previous in vitro studies indicate that curcuminoids and piperine (a black pepper derivative that enhances curcuminoid bioavailability) could inhibit human CYP3A, CYP2C9, UGT and SULT dependent drug metabolism. The aim of this study was to determine whether a commercially available curcuminoid/piperine extract alters the pharmacokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 46 publications
(60 reference statements)
4
38
0
3
Order By: Relevance
“…Piperine is efficiently absorbed by the gut and is widely distributed in the various tissues (29,30). However, most of the piperine has been conjugated with glucuronic acid, which may influence its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Piperine is efficiently absorbed by the gut and is widely distributed in the various tissues (29,30). However, most of the piperine has been conjugated with glucuronic acid, which may influence its activity.…”
Section: Discussionmentioning
confidence: 99%
“…The dichotomous effects of PIP could help explain the observations from several clinical studies attempting to use PIP as a bioavailability enhancer for drugs that are CYP3A4 substrates. A recent human study showed that an herbal extract containing PIP (24 mg) failed to enhance the bioavailability of midazolam (a CYP3A4-selective substrate); the plasma pharmacokinetics of midazolam remained unchanged in the presence of PIP (Volak et al, 2013). Similarly, in two other human studies, co-administration of 20 mg PIP showed no significant inhibition on the rate of metabolism of two CYP3A4 substrates, nevirapine (200 mg) and carbamazepine (500 mg), as indicated by the unchanged elimination constant rate (K el ) (Kasibhatta and Naidu, 2007; Pattanaik et al, 2009), suggesting that PIP at this dose probably had no significant effect on inhibiting CYP3A4 activity in human.…”
Section: Discussionmentioning
confidence: 99%
“…We selected acetaminophen [since its main metabolic pathway is glucuronidation by UGT1A1/1A6/1A9 (Court et al 2001) and also UGT2B15 (Navarro et al 2011)], instead of a more specific substrate of only one UGT isoform because acetaminophen is widely available, inexpensive and well tolerated, and also because these three UGT1A isoforms are involved in the metabolism of many clinically relevant drugs. In the case of lack of change in the acetaminophen/acetaminophen glucuronide phenotyping index, the investigator will have relevant information on the UGT1A pool, as previously studied using acetaminophen as a probe (Volak et al 2013). In the case that there is a change, additional investigations could be performed using more specific probes such as endogenous bilirubin (UGT1A1) or propofol (UGT1A9) as already reported in neonates (Allegaert et al 2009).…”
Section: Discussionmentioning
confidence: 99%